2021
DOI: 10.29271/jcpsp.2021.04.399
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-inflammation Index (SII) Predicts Pathological Complete Response to Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer

Abstract: Objective: To determine the relationship between inflammatory markers and pathological complete response (pCR) in patients with locally advanced rectal cancer (LARC), who received neoadjuvant chemoradiotherapy (NACRT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Meanwhile, LMR and PLR at post-treatment in the third period seemed to have a more balanced prediction probability for ESCC patients who had responded or no response; thus, there was a more ideal prediction probability in combining LMR with PLR at post-treatment in the third period. Prior studies reported that SII at baseline might predict pCR status for neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer [ 33 ], and non-small cell lung cancer patients with preoperative high SII levels benefit from adjuvant chemotherapy [ 34 ], which suggests a certain degree of consistency with our results. However, we attempted to combine these inflammation indices to determine whether they could predict the efficacy, instead of using a single or dual biomarkers.…”
Section: Discussionsupporting
confidence: 84%
“…Meanwhile, LMR and PLR at post-treatment in the third period seemed to have a more balanced prediction probability for ESCC patients who had responded or no response; thus, there was a more ideal prediction probability in combining LMR with PLR at post-treatment in the third period. Prior studies reported that SII at baseline might predict pCR status for neoadjuvant chemoradiotherapy in patients with locally advanced rectal cancer [ 33 ], and non-small cell lung cancer patients with preoperative high SII levels benefit from adjuvant chemotherapy [ 34 ], which suggests a certain degree of consistency with our results. However, we attempted to combine these inflammation indices to determine whether they could predict the efficacy, instead of using a single or dual biomarkers.…”
Section: Discussionsupporting
confidence: 84%
“…In the presented study, unlike other studies, it has been shown that lymphocyte level can also be a marker in predicting pCR [24]. From our point of view, the high number of patients in this study may have made a difference in obtaining this result [24]. Moreover, in our study, similar to other studies, NLR and PLR were independent predictive factors after adjustment for confounding factors [15,16].…”
Section: Discussionsupporting
confidence: 66%
“…There are several other studies suggesting that systemic inflammatory indices such as NLR and PLR are predictors of the pathological response to neoadjuvant CRT [ 15 - 16 , 28 - 29 ]. In the presented study, unlike other studies, it has been shown that lymphocyte level can also be a marker in predicting pCR [ 24 ]. From our point of view, the high number of patients in this study may have made a difference in obtaining this result [ 24 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Jiang et al [ 8 ] retrospectively analyzed 387 female patients with breast cancer who were treated with NACT followed by surgery and determined that the SII was an independent predictor of pCR for patients with breast cancer, with the low-SII group showing the highest pCR rate. Eraslan et al [ 9 ] studied 188 patients diagnosed with locally advanced rectal cancer who received neoadjuvant chemoradiotherapy (NACRT) and found that among several inflammatory indices, including neutrophil-to-lymphocyte ratio (NLR), PLR, and SII, only the SII, at a value of <748, was an independent predictive factor of pCR after NACRT (OR: 0.471, 95% CI: 0.224–0.991, p = 0.047). Murthy et al [ 11 ] found that the SII could reflect treatment response and outcome following NACT for patients with pancreatic adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%